Analysis of the Effectiveness of Midwifery Care in Health Observations of 24-Month-Old Toddlers: Study in Kute Rayang Village, Central Aceh, Indonesia - Irdayani; Widya Apriani; MS, Sri Wahyuni (Community Medicine and Education Journal, 2024)
Toddler health is an important indicator of public health and nation development. Midwifery care plays an important role in maintaining the health of toddlers, including observing the health of toddlers aged 24 months. This study aims to analyze the effectiveness of midwifery care in observing the health of 24-month-old toddlers in Kute Rayang Village, Central Aceh, Indonesia. This study used a cross-sectional observational design with a sample of 100 toddlers aged 24 months who were selected at simple random. Data was collected through interviews, observation, and physical examination. Data analysis was carried out using Chi-square and T-test. The results showed that midwifery care in observing the health of 24-month-old toddlers in Kute Rayang Village, Central Aceh, Indonesia was quite effective. As many as 80% of toddlers have undergone complete health observation by midwives. Observation of toddler health has increased complete immunization coverage (p<0.05), nutritional status of toddlers (p<0.05), and maternal knowledge about toddler health (p<0.05). Midwifery care in health observations for 24-month-old toddlers in Kute Rayang Village, Central Aceh, Indonesia is quite effective, but can still be improved. Increasing the effectiveness of midwifery care can be done through various efforts, including increasing the knowledge and skills of midwives, increasing community access to health services, and increasing community participation in maintaining the health of toddlers.